CORRELATIVE PARALLELS IN GREEK AND YORÙBÁ GREAT GODDESS TRADITIONS (2012)
Increasing interests in comparative studies have led scholars to revisit the myth of the Great Goddess. While parallels of the Greek gods have been identified in Yorùbá mythology, there has not been a comparative study of the Great Goddesses. This study, therefore, examines the parallels between the Greek’s Great Goddess, Gaea, and Àtàgé, the Yorùbá Great Goddess of Ìbàdàn, to determine points of convergence between them in terms of origin, attributes, symbols and festival, confirming the existence of a Yorùbá Great Goddess. The study adopted Jung’s Archetypal Theory. Works of Greek mythographers including Homer, Hesiod, Appolodorius, Appolonius; Yorùbá historians like Johnson, Falola, Awe, Parrinder; and certain verses of the Yorùbá Ifá corpus were content analysed for parallels on the Great Goddesses. The study applied participant observation technique. Unstructured interviews were also conducted with Abòkè, High Priest of Àtàgé, and nine of the omo òkè to verify those attributes not described in the literature. Information obtained was qualitatively interpreted. There was evidence of similarities of the evolved aspects of Gaea and the Yorùbá’s Àtàgé, notably in origin, attributes, symbols and festival. While Gaea was extensively discussed, literature had little on Àtàgé. It, however, described Àtàgé as the spirit behind the foundation of Ìbàdàn as Gaea began the universe in Greek’s cosmogony; suggested Àtàgé as Goddess of Ibadan land known for motherhood, human, animal and soil productivity similar to Gaea’s; made references to the pitcher-breasted image of the Great Goddess capable of feeding sixteen children at once; and the annual sacred orgasm festival of Àtàgé which continued even to the present. This festival took place about the time of spring vernal equinox resembling that of Gaea and all other known archetypes of the Great Goddess. During such festivals, celebrants venerated Àtàgé as the origin, mother and protector of Ìbàdàn indigenes as Gaea was so honoured by the Greeks. Phallic symbols like those of the Greek’s Goddess festivals were carried while the procession prayed to Àtàgé for healthy children, safety and abundance in wealth. Led by transvestite priest, reminiscent of the Greek’s, they danced round the town, singing ribald songs and making gesticulations capable of stimulating sexual desire. The Priest, with plaited hair, confirmed that Àtàgé had a covenant with Lágelú, the legendary founder of Ìbàdàn, to protect and bless the town. As the functions of Gaea were taken by Zeus, the priest gave evidence that Àtàgé originally had a priestess before the role was taken over by a priest. The importance of the annual festival in relation to fertility, protection and success of the indigenes was corroborated. UNIVERSITY OF IBADAN LIBRARY x Àtàgé has similar origin, attributes, symbols and festivals as the Greek’s Gaea. The significance of Àtàgé in Ìbàdàn presupposes the presence of a Yorùbá prehistoric matriarchal society and confirms the existence of a Yorùbá Great Goddess. Key words: Great Goddess, Ìbàdàn, Gaea, Àtàgé. Word count: 460.